Characterisation and comparative analysis of MHC-DPA1 exon 2 in the owl monkey (Aotus nancymaae) (2011)
The Aotus nancymaae (owl monkey) is an important animal model in biomedical research, particularly for the preclinical evaluation of vaccine candidates against Plasmodium falciparum and Plasmodium vivax, which require a precisely typed major histocompatibility complex. The exon 2 from A. nancymaae MHC-DPA1 gene was characterised in order to infer its allelic diversity and evolutionary history. Aona-DPA1 shows no polymorphism and is related to other primate DPA alleles (including Catarrhini and Platyrrhini), constituting an ancient trans-specific and strongly supported lineage with different variability and selective patterns when compared to other primate-MHC-DPA1 lineages. A. nancymaae monkeys have thus a smaller MHC-DP polymorphism than MHC-DQ or MHC-DR. © 2010 Elsevier B.V.